Alternative program to improve reading comprehension in schoolchildren peruvian - Chong Alvarado, Lis Norma (2021)
This article presents the results of an investigation that tests an alternative program to improve reading comprehension, the direct instruction of reading strategies, the use of different types of texts, and where the teacher cedes control of the process were taken as guidelines reader to student gradually. The research was of an applied type, with a quasi-experimental design, working with 44 second-grade high school students from public educational institutions, to measure the study variable of applying the Demonstrating what we learned-Reading test developed by the UMC. The results show us a significant difference between the control and experimental group, proving its effectiveness in increasing the level of reading comprehension and in the development of their abilities.